Getting the focus right: achieving the targeted compensation of employees' composition in post-mid-term review of the Twelfth Malaysia Plan - Utit, Chakrin; Ismail, Normaz Wana; Idris, Zera Zuryana (School of Business and Economics, Universiti Putra Malaysia, 2023)
The successful implementation of eleven Malaysia Plans in charting and navigating economic growth has seen the transformation of Malaysia from an agricultural economy to an industrialised one and subsequently into a services-based economy. However, despite the developmental progress, Malaysia's growth quality was highly debatable due to the lower implications of growth on the compensation of employees (COE) generation. In line with the mid-term review of the Twelfth Malaysia Plan (12MP), this study was structured to reassess the sectoral capacity towards supporting the achievement of 40 targeted COE composition. Applying the reassessment models developed based on the input-output modelling technique yields positive outcomes, with 19 sectors central to COE target achievement identified. The sectors were grounded based on three areas of potential that are capable of guiding policy decisions to improve the COE composition: (i) sectors that have achieved the 40 targeted COE composition with strong backward (BW) and forward (FW) linkages; (ii) sectors that have achieved the 40 targeted COE composition with strong BW or FW linkage; and (iii) sectors over 30 achieved COE composition with strong BW or FW linkage, or both.